Government debt, human capital, and endogenous growth' - Zhang, Jie (School of Management Working Papers, 1995)
This paper examines the effect of government debt on steady-state per capita growth in an endogenous growth model. When fertility is exogenous, government debt has no effect on growth. However, when fertility is endogenous, government debt causes faster growth by reducing fertility and by stimulating human capital investments. Due to its distorting effects, government debt reduces initial welfare but it increases future generations' welfare through increasing the growth rate. To maintain a constant debt income ratio supported by taxes and to maintain a stable population, governments cannot raise debt relative to income limitlessly.